2014
DOI: 10.15253/2175-6783.2014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic, clinical and laboratory profile of patients submitted to hemodialysis

Abstract: The aim of the study was to characterize the patients with Chronic Kidney Disease submitted to hemodialysis in Rio Grande do Sul, Brazil, regarding the socio-demographic, clinical and laboratory characteristics. It is a cross-sectional study with 90 hemodialysis patients made in July and August 2013, through interviews. The results showed that 77.8% of the patients were male, with average age of 53.52 years and 66.7% were married. The average of schooling was 6.61 years; the Unified Health System assisted 86.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…20 In relation to underlying CRD disease and association of comorbidity, systemic arterial hypertension (SAH) has also been found in other studies. [21][22] SAH has become a national and worldwide public health problem and is considered a ubiquitous condition in CRD, and can be considered a cause and consequence of such pathology. 23 The choice of the dialysis modality is associated with several factors, and it is of fundamental importance that the patient knows the types of treatments offered for a joint definition of the treatment, associated with the clinical condition of the patient and the doctor´s evaluation 6 .…”
Section: /13mentioning
confidence: 99%
“…20 In relation to underlying CRD disease and association of comorbidity, systemic arterial hypertension (SAH) has also been found in other studies. [21][22] SAH has become a national and worldwide public health problem and is considered a ubiquitous condition in CRD, and can be considered a cause and consequence of such pathology. 23 The choice of the dialysis modality is associated with several factors, and it is of fundamental importance that the patient knows the types of treatments offered for a joint definition of the treatment, associated with the clinical condition of the patient and the doctor´s evaluation 6 .…”
Section: /13mentioning
confidence: 99%
“…Neste estudo observou-se que a maioria dos pacientes submetidos à hemodiálise eram do sexo masculino, o que corrobora com estudos em diversas localidades no Brasil [32,33,34,35]. Em um estudo com população japonesa, foi observado que a obesidade sem anormalidades metabólicas estava associada com maior risco de DRC em homens [36].…”
Section: /7unclassified
“…3,6,8 The greater prevalence of men in the process of hemodialysis occurs by their lower frequency in health services, thus, the late diagnosis of a CKD leads to a poor prognosis. 9 This therapy is performed in older adults once the greater the age, the higher the probability of being affected by chronic diseases such as diabetes mellitus and hypertension, which provides gradual onset of a CKD and consequently adherence to a treatment. 2,10 Other studies corroborate the results of this work, regarding race, in which pardos showed greater adherence to both hemodialysis, as well as to the pharmacological treatment.…”
Section: Introductionmentioning
confidence: 99%